Perkembangan Kewirausahaan Pada Mahasiswa Universitas Lancang Kuning Pekanbaru Berbasis Teknologi - Abrar Tanjung; Ganefri Ganefri (Forum Dosen Indonesia, 2020)
Technopreneur one part of the development of entrepreneurship (entrepreneur) provides an overview of entrepreneurship by using technology-based innovation. The concept of technopreneur is based on a technology base that is used as an entrepreneurial tool, for example the emergence of an online application business and business security system. The purpose of this study is to conduct a descriptive study of entrepreneurship on students using technology (Technopreneurship) from all points of view, whether motivation, ownership, managerial, employment, and so on. technology as a basis for entrepreneurship. The results of the discussion found that the use of technology (Technopreneurship) in entrepreneurship can help and develop businesses in the form of product production and marketing of product results, so as to increase student income. Keywords: Technopreneur, entrepreneurship, students